2020
DOI: 10.1587/transinf.2020edl8020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EEG Activation Pattern on the Experience of Visual Perception in the Driving

Abstract: The brain processes numerous information related to traffic scenes for appropriate perception, judgment, and operation in vehicle driving. Here, the strategy for perception, judgment, and operation is individually different for each driver, and this difference is thought to be arise from experience of driving. In the present work, we measure and analyze human brain activity (EEG: Electroencephalogram) related to visual perception during vehicle driving to clarify the relationship between experience of driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…As a result, higher traffic-collision rates are reported for beginner drivers compared with for experienced drivers. We recently reported that the EEG activation patterns of drivers are uniquely altered between experienced and beginner drivers [ 34 ]. Moreover, the estimated gamma-band functional connectivity from EEG recordings of the whole-brain area is entirely different between experienced and beginner drivers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, higher traffic-collision rates are reported for beginner drivers compared with for experienced drivers. We recently reported that the EEG activation patterns of drivers are uniquely altered between experienced and beginner drivers [ 34 ]. Moreover, the estimated gamma-band functional connectivity from EEG recordings of the whole-brain area is entirely different between experienced and beginner drivers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of driving experience is complicated. In this study, to investigate the effects of driving experience, the subjects were divided into experienced and beginner drivers on the basis of their driving frequency and the duration for which they have held a driver’s license [ 2 ], which is the same definition as that in our previous study [ 34 , 35 ]. In this study, our experienced subjects had driven more than five times per week and maintained a valid driver’s license for at least three years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations